Thermal energy storage design of a new bifacial PV/PCM system for enhanced thermo-electric performance - Akshayveer; Kumar A.; Pratap Singh A.; Sreeram Kotha R.; Singh O.P. (My University, 2025)
A new concept of bifacial PV/PCM (BIF-PV/PCM) system with sandwiched thermal energy storage enclosure has been investigated that possesses 1.21 times power output density and 7.39 times total energy utilization density per unit land area compared to the conventional PV system. Based on the melting morphology and thermo-electric performance of the initially rectangular PCM enclosure, an optimized bifurcated non-rectangular design of the enclosure is proposed to enhance the incident radiation utilization ability by 87% more than a simple one PV/PCM system. Enhanced utilization of solar radiation manifests into 105% more melting compared to conventional PV/PCM system. With the strategic mirror reflection and bypassing the solar radiation towards the rear PV panel and strategic design of PCM enclosure to aid convection-driven melting, electric power output has been increased significantly (about 77%) compared to similar conventional PV/PCM system. The study revealed that overall system efficiency could approach about 74% if suitable strategies are adopted, as demonstrated in this paper. Results are discussed in terms of energy utilization efficiency, exergy efficiency, power conversion efficiency, tracking melting front morphology, and its effect on heat transfer characteristics, etc. This investigation has been carried out with the help of an experimentally calibrated numerical model that accurately mimics the melting morphology of PCM and other heat transfer characteristics of the system. The findings of this study would help design and develop a more efficient BIF-PV/PCM system to meet exponentially increasing energy needs. © 2021 Elsevier Ltd